Smoking Behavior Among High School Students In Padang City - Arlinda Sari (International Journal of Health Engineering and Technology, 2022)
Youth is a phase of transition from children to adults, marked by the acceleration of physical, mental, emotional, and social development. They are still looking for self-identity, tend to follow trends, are still unstable, and are very easily influenced by peers, including the influence of smoking. This study aims to determine the influence of knowledge, pocket money, access to cigarettes, mass media, family, and peers to smoking behaviour among high school students in the city of Padang. The method of this study is a cross-sectional survey by interviewing 220 male students in 5 (five) Public High Schools in Padang City who were selected by multistage random sampling. Data was collected using a structured questionnaire that had been tested for validity and reliability. Multiple logistic regression is used to determine the relationship. The study showed 59.1% of high school male students in Padang smoked. Most of them them have knowledge about smoking (62.3%) and are exposed to cigarette advertisements in the mass media (52.3%), have peers smokers (60.5%), and have families who smoke (51.4%) . Students who have peers smokers 10.1 times more likely to start smoking (OR 10.1, 95% CI 5.5 - 19.5). Knowing that adolescents first smoke at the age of 7 years and peer behavior is the biggest risk factor for starting smoking in adolescents, precautionary measures are recommended, such as health counseling as early as possible (starting in primary or secondary school).